The Road to Survival for Haemodynamically Unstable Patients With Open Pelvic Fractures - Watkins, Rachel J.; Hsu, Jeremy M. (Frontiers in Surgery, 2020)
Management of haemodynamically unstable pelvic ring injuries has been simplified into treatment algorithms to streamline care and emergent decision making in order to improve patient outcomes whilst decreasing mortality and morbidity. Pelvic ring injuries are most commonly a result of high-velocity and energy forces that exert trauma to the pelvic bones causing not only damage to the bone but the surrounding soft-tissue, organs and other structures and are usually accompanied by injuries to other parts of the body resulting in a polytraumatised patient. Open pelvic fractures are a rare subset of pelvic ring fractures that are on the more severe end of the pelvic fracture continuum and usually produce uncontrolled haemorrhage from fractured bone, retroperitoneal haematomas, intraabdominal bleeding from bowel injury, soft tissue injuries to the anus, perineum and genitals, fractures of the pelvic bones, causing bleeding from cancellous bone, venous and arterial injuries combined with bleeding from concomitant injuries. This is a very complex and challenging clinical situation and timely and appropriate decisions and action are paramount for a positive outcome. Consequently, open pelvic fractures have an extremely high rate of mortality and morbidity and outcomes remain poor, despite evidence-based improvements in treatment, knowledge and identification of haemorrhage; in the pre-hospital, critical care and operative settings. In the future utilisation of haemostatic drugs, dressings, devices and procedures may aid in the time to haemorrhage control.